Rare Case of Metastatic Pleomorphic Liposarcoma of Thigh Presenting as Ewing’s Sarcoma - Giri , Sandip; Gehani, Anisha; Alphones , Sheena; Midha, Divya; Baral, Dibash (Journal of Nepal Health Research Council, 2021)
Liposarcoma is an uncommon group of tumors in the pediatric population. Of the various known subtypes,pleomorphic liposarcoma is the most infrequent in children.We present the case of a 7-year old child coming to the radiology department for evaluation of a right knee swelling. Plain radiograph and corresponding MRI images showed features of primary bone tumor possibly Ewing’s sarcoma in right distal femur. The child developed right shoulder pain and CT thorax abdomen was done which revealed retroperitoneal mass with hepatic and pulmonary metastases.Subsequent core needle biopsy from the femur confirmed metastatic liposarcoma with pleomorphic features, extremely rare in childhood.The very rare incidence of metastasis that too presenting as a common primary tumor the misdiagnosis of which could result in catastrophic fate. So it’s of prime importance that clinicians should be aware of this entity. Keywords: FISH; liposarcoma; myxiod dedifferentiated liposarcoma; pleomorphic liposarcoma; softsarcoma